Composite photocathode for photoelectrochemical hydrogen evolution reaction, photoelectrochemical cell comprising the same, and the process thereof

KR103022423B1Active Publication Date: 2026-09-22KOREA INST OF ENERGY TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020260019848
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-09-22
Estimated Expiration
2046-01-30

Smart Images

  • Figure 112026013414948-PAT00001_ABST
    Figure 112026013414948-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a p-type semiconductor / ceramic composite photocathode of Formula 1 for a photoelectrochemical hydrogen generation reaction, a photoelectrochemical cell comprising the same, and a method for manufacturing the same. Through various embodiments of the present invention, it is possible to ultimately achieve the production of green hydrogen through photoelectrochemical water splitting with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a composite photocathode for a photoelectrochemical hydrogen generation reaction, a photoelectrochemical cell including the same, and a method for manufacturing the same, etc. Background Technology

[0002] The energy crisis is one of the significant problems facing the modern world, and it is a problem that must be solved to meet the increasing energy demand resulting from industrial growth and population increase.

[0003] Recently, much research has been conducted on the development of clean renewable energy through photoelectrochemical (PEC) water splitting. Among all fuels, hydrogen fuel has the highest gravimetric energy density and is used as clean energy in the transportation, manufacturing, and various other sectors.

[0004] However, for commercial feasibility, photoelectrode materials must exhibit a Solar-To-Hydrogen (STH) conversion efficiency of more than 10%, but the STH conversion efficiency has not met the requirements for practical application.

[0005] To date, various semiconductor-based photocathodes have been used in the Hydrogen Evolution Reaction (HER), and significant efficiency has been achieved in converting light energy into useful chemicals and electricity. Representative photocathode materials include silicon (Si), gallium phosphide (GaP), copper-based oxides, metal sulfides, metal phosphides, and carbon-based semiconductors.

[0006] In particular, copper(I) oxide (Cu2O) has a band gap of about 2.0 eV and exhibits excellent light absorption characteristics in the visible region of the solar spectrum. It is composed of abundant elements and has a conduction band position suitable for hydrogen evolution reactions as a p-type semiconductor, so it is attracting attention as a promising photocathode material.

[0007] However, the activation of single metal oxides is limited, and there is a problem in that Cu2O photocathodes experience severe photocorrosion and poor chemical stability under aqueous operating conditions. Furthermore, solar-to-hydrogen conversion efficiency is limited due to inefficient charge separation and rapid charge recombination.

[0008] To enhance HER activity, precious metal co-catalysts such as platinum (Pt), palladium (Pd), or ruthenium (Ru) have been deposited on the photocathode surface, but large-scale economical deployment is hindered due to the high cost and limited availability of these co-catalysts.

[0009] Furthermore, many reported manufacturing methods involve complex multi-step processes, high-temperature treatments, or vacuum-based deposition techniques, which are not suitable for large-area or scalable manufacturing.

[0010] Therefore, despite continuous advancements, existing HER photocathode technology is still facing challenges due to insufficient efficiency, limited operational stability, high material costs, and poor scalability. Accordingly, there is a need to develop new photocathode materials and manufacturing methods that can overcome these limitations. Prior art literature

[0011] 1. Chinese Published Patent No. 117822013 2. Chinese Published Patent No. 117845264 3. Korean Published Patent No. 10-2023-0030188

[0012] 1. Applied Catalysis B: Environmental 243 (2019): 657-6662. Chemistry of Materials (2024), 36(1), 275-285 The problem to be solved

[0013] The present invention aims to solve the technical problems of the existing technologies described above and to provide a p-type semiconductor / ceramic composite photocathode for photoelectrochemical hydrogen generation reactions having excellent performance, a photoelectrochemical cell including the same, a water splitting device, a hydrogen generation device, and a method for manufacturing the photocathode, and ultimately to achieve green hydrogen production through photoelectrochemical water splitting.

[0014] Specifically, the objectives of the present invention are as follows: (i) to develop an efficient and durable photocathode based on a novel composite material synergistically combined with a co-catalyst to improve HER performance; (ii) to achieve a benchmark level of photocurrent density for hydrogen generation reaction that is comparable to or exceeds that of state-of-the-art photocathode materials under simulated solar irradiation; (iii) to increase charge carrier density within the photocathode and improve charge separation efficiency through material composition control and interface engineering; and (iv) to maximize hydrogen generation efficiency and long-term stability by optimizing scalable photocathode operating and manufacturing parameters, including co-catalyst loading amount, film thickness, annealing conditions, electrolyte composition, and operating temperature. means of solving the problem

[0015] One aspect of the present invention relates to a composite comprising a p-type semiconductor oxide and a ceramic of the following chemical formula 1.

[0016] [Chemical Formula 1]

[0017] Pb 10-x Cu x [(PO4) 6-y (SO4) y ]O z S z'

[0018] x is a real number between 0.9 and 9.9, and y is 10 -10 It is a real number from 5.9 to 10, where z and z' are each 10 -10 It is a real number between 4 and 10, and z+z' is 10 -10 It is a mistake of up to 4.

[0019] In this specification, 'ceramic' means a substance represented by Chemical Formula 1 unless otherwise specified.

[0020] Another aspect of the present invention relates to a photoactive material comprising a composite according to various embodiments of the present invention.

[0021] Another aspect of the present invention relates to a photocathode comprising (a) a substrate and (b) a photocathode layer formed on at least a portion of the surface of the substrate and comprising a composite according to various embodiments of the present invention.

[0022] Another aspect of the present invention relates to a photoelectrochemical (PEC) cell comprising (i) a working electrode, (ii) a counter electrode, and (iii) a reference electrode, wherein the working electrode is a photocathode according to various embodiments of the present invention.

[0023] Another aspect of the present invention relates to a water splitting device comprising a photoelectrochemical cell according to various embodiments of the present invention.

[0024] Another aspect of the present invention relates to a method for manufacturing a photocathode comprising the steps of: (A) forming a coating layer by coating a substrate with a mixed solution comprising (a1) a p-type semiconductor oxide precursor and (a2) a ball-milled powder dispersion of a ceramic represented by Formula 1; (B) forming a coating layer by heating the coating layer; and (C) forming a photocathode layer by firing the coating layer in an inert atmosphere.

[0025] Another aspect of the present invention relates to a co-catalyst for a photoelectrochemical hydrogen generation reaction comprising a ceramic of Formula 1.

[0026] Another aspect of the present invention relates to a photoelectrochemical hydrogen generation method comprising the step of generating hydrogen from water under light irradiation using a photocathode according to various embodiments of the present invention. Effects of the invention

[0027] According to various embodiments of the present invention, the technical problems of the prior art described above are resolved, and a composite photocathode for a photoelectrochemical hydrogen generation reaction having excellent performance, a photoelectrochemical cell including the same, and a method for manufacturing the same are provided, and ultimately, green hydrogen production can be achieved through photoelectrochemical water splitting.

[0028] From the perspective of solar energy utilization, photoelectrochemical water splitting systems employing two or more different semiconductor materials or composite structures are superior to single-semiconductor electrode-based systems. In particular, heterostructures or composite photocathodes provide improved band alignment and an effectively extended light absorption range, enabling the utilization of a wider portion of the solar spectrum.

[0029] Furthermore, integrating additional functional components into the semiconductor photoelectrode increases the interfacial contact area for photogenerated charge carriers, improves charge separation efficiency, and induces a synergistic effect that suppresses electron-hole recombination.

[0030] Therefore, to achieve high photocurrent densities for the hydrogen evolution reaction (HER) in photoelectrochemical water splitting, it is necessary to develop efficient and inexpensive photocathode materials with appropriate visible light absorption capabilities, improved charge carrier transport, and enhanced surface reaction kinetics.

[0031] The present invention provides a p-type semiconductor / ceramic-based photoelectrochemical hydrogen generation system that overcomes the limitations of existing technology and offers the following technical advantages.

[0032] First, the photoelectrochemical water splitting system according to the present invention enables hydrogen production from water through a solar-driven electrochemical reaction, thereby providing a clean, sustainable, and environmentally friendly method for generating hydrogen without consuming fossil fuels.

[0033] Second, by incorporating an optimized amount of ceramic (ceramic of Formula 1) inside or on a p-type semiconductor-based photocathode, the present invention significantly improves charge separation and electron transport within the photocathode. The p-type semiconductor / ceramic composite structure forms improved interfacial contacts that promote the efficient transfer of photogenerated electrons toward the electrode-electrolyte interface, thereby increasing the photocurrent density for the hydrogen evolution reaction. Consequently, relatively high solar-to-hydrogen conversion efficiency can be achieved under optimized operating conditions.

[0034] Third, the p-type semiconductor / ceramic photocathode of the present invention can be manufactured using a cost-effective and simple electrostatic spray deposition process that enables uniform ceramic distribution and precise control of thin film thickness without complex vacuum-based equipment. This significantly reduces manufacturing costs and improves scalability compared to existing manufacturing methods.

[0035] Fourth, the photoelectrochemical system of the present invention improves operational safety and gas collection efficiency by adopting spatially separated photoelectrodes, thereby allowing for the effective separation of hydrogen and oxygen generated during the water splitting reaction. In addition, the reactor structure is flexible in size and configuration, making it suitable for small-scale modular hydrogen production as well as large-scale applications.

[0036] Fifth, the p-type semiconductor / ceramic composite photocathode of the present invention exhibits a photocurrent density approximately twice that of a pure Cu2O photocathode, which is attributed to the improvement in electrical conductivity and charge carrier transfer due to the introduction of ceramic.

[0037] Accordingly, the present invention provides a p-type semiconductor / ceramic-based photoelectrochemical hydrogen generation system that achieves improved photocurrent density, improved solar-hydrogen efficiency, reduced manufacturing cost, and excellent applicability compared to conventional single-semiconductor photocathode technology. Brief explanation of the drawing

[0038] Figure 1 is a schematic diagram showing the detailed experimental process of a Cu2O / ceramic photocathode. It shows the deposition of a precursor solution using an electrostatic spray deposition (ESD) device, the annealing process in an inert atmosphere, and the configuration of a photoelectrochemical water splitting system. Figure 2 shows scanning electron microscope (SEM) images. (a and b) SEM images of a pure Cu2O thin film, (c) cross-sectional image of pure Cu2O, (d and e) scanning electron microscope images of a Cu2O / ceramic composite thin film, (f) cross-sectional image of a Cu2O / ceramic composite. Figure 3 shows the XPS spectra for pure Cu2O and Cu2O / ceramic composite photocathodes. (a) Cu 2p, (b) O 1s, (c) Pb 4f (complex), (d) S 2p (complex). Figure 4 shows the photoelectrochemical measurement results for pure Cu2O and Cu2O / ceramic composite photocathodes. (a) Linear Scanning Potential (LSV) curve, (b) Chopped curve. The unit of the Y-axis of the graph is mA / cm². Specific details for implementing the invention

[0039] Below, various aspects and embodiments of the present invention will be examined in more detail.

[0040] Expressions such as 'comprising,' 'having,' 'consisting of,' and 'composed of' in this specification may have additional parts added unless 'only' is used. Furthermore, numerical values ​​or numerical ranges described in this specification are interpreted to include a margin of error unless otherwise explicitly stated. Additionally, expressions 'X to Y' indicating a numerical range in this specification mean 'X or greater and Y or less.'

[0041] Embodiments of the present invention will be described in detail below with reference to the drawings. However, detailed descriptions of known functions or configurations that may obscure the essence of the present invention in the following description and the attached drawings are omitted. Additionally, throughout the specification, the term 'comprising' a component means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0042] Unless specifically defined otherwise, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.

[0043] One aspect of the present invention relates to a composite comprising a p-type semiconductor oxide and a ceramic of Formula 1.

[0044] The ceramic of Chemical Formula 1 above can be used as a composite with a p-type semiconductor oxide according to various aspects and embodiments of the present invention, as a photocathode, particularly for a hydrogen evolution reaction (HER); as a photoelectrochemical cell, particularly for water splitting or hydrogen evolution; and as various other multifunctional materials.

[0045] If some of the components constituting the ceramic are omitted or fall outside the compositional range, it is undesirable in that, unlike the ceramic of Formula 1, it is not effective for separating charge carriers and the synergistic effect between the p-type semiconductor oxide and the ceramic may not be observed at all, and thus the effects according to various aspects and various embodiments of the present invention cannot be fully expressed.

[0046] Examples of p-type semiconductor oxides usable in the present invention include, but are not limited to, Cu2O, CuO, Cu2O / CuO composites, NiO, Co3O4, and combinations of two or more of these. However, in the case where the p-type semiconductor oxide in the present invention is Cu2O, it is preferred in that Cu2O has an appropriate band gap of about 2.0 eV and exhibits excellent light absorption characteristics in the visible light region, is cost-effective as it is composed of elements abundant on Earth, and has a conduction band position suitable for hydrogen evolution reactions as a p-type semiconductor, thereby maximizing synergistic effects when forming a composite with the ceramic of Formula 1.

[0047] According to one embodiment, x in the above chemical formula 1 is 2.1-9.9.

[0048] Specifically, when x satisfies the range of 2.1 to 9.9, the bandgap energy of the ceramic of Formula 1 is reduced by Cu doping, thereby improving electrical conductivity. Consequently, a synergistic effect that cannot be predicted with the p-type semiconductor oxide alone or the ceramic alone is manifested in the composite with the p-type semiconductor oxide, thereby promoting the efficient transfer of photogenerated electrons at the interface between the p-type semiconductor oxide and the ceramic, which suppresses charge recombination and achieves improved photocurrent density and improved hydrogen generation performance. On the other hand, when x is less than 2.1, the improvement in electrical conductivity is insufficient due to the lack of Cu doping, so the above synergistic effect is not sufficiently manifested. When x exceeds 9.9, the crystal structure stability of the ceramic is reduced, making it difficult to form a uniform composite with the p-type semiconductor oxide and the above synergistic effect may not be observed. Therefore, it is desirable to satisfy the range of x 2.1 to 9.9.

[0049] According to another embodiment, the composite comprises the p-type semiconductor oxide and the ceramic of Formula 1 in a ratio of 0.04 to 400 mmol per 1 mol of the p-type semiconductor oxide. If the ratio is below the lower limit of the range or exceeds the upper limit, the electrode containing the composite may not have a significant effect on improving electron mobility at the electrode-electrolyte interface and charge carrier separation efficiency compared to a pure Cu2O electrode, which is undesirable.

[0050] However, in the present invention, the above complex is the p-type semiconductor oxide ~1-1.5 It is desirable that the p-type semiconductor oxide and the ceramic of Formula 1 are included in a ratio of 0.25-0.55 mmol of the ceramic of Formula 1 based on molar, in that the effect of improving charge separation efficiency and the effect of improving electron mobility are optimized, thereby maximizing photoelectrochemical hydrogen generation performance.

[0051] A composite according to another embodiment of the present invention, as a result of X-ray photoelectron spectroscopy (XPS) analysis, Cu(2p 3 / 2 ) The binding energy was observed at approximately 932-933 eV, so Cu + The state can be confirmed, and through the presence of the Pb(4f), Cu(2p), S(2p), and P(2p) peaks, it can be confirmed that the ceramic component of Formula 1 is uniformly distributed within the composite.

[0052] According to another embodiment, as a result of dynamic light scattering (DLS) analysis, the ceramic has an average particle size of 500-1,500 nm and a full width at half maximum of 1,000 nm or less. This is related to the ball milling conditions described below, and when the ball milling conditions are particularly 400-700 rpm and 3-36 hours, the average particle size according to DLS analysis becomes uniform at 500-1,500 nm and the full width at half maximum of 1,000 nm or less, which may be advantageous for further improving photoelectrochemical performance when utilized in a photocathode.

[0053] However, as a result of dynamic light scattering (DLS) analysis, if the ceramic has an average particle size of 500-1,500 nm and a full width at half maximum of 500 nm or less, it is desirable in that the particle size distribution becomes more uniform, thereby improving reaction uniformity at the electrode-electrolyte interface and further optimizing photoelectrochemical performance. This is also related to the ball milling conditions described below; specifically, when the ball milling conditions are 450-550 rpm and 5-7 hours, the average particle size according to DSL analysis becomes 500-1,500 nm and the full width at half maximum of 500 nm or less, making it more uniform, which can be advantageous for further improving photoelectrochemical performance when utilized in a photocathode.

[0054] In particular, when the particle width at half maximum (FWHM) is 500 nm or less, compared to when it is 1,000 nm or less, a heterogeneous effect is exhibited in which the interfacial contact area between the p-type semiconductor oxide and the ceramic is significantly increased and the charge transport path is optimized, thereby drastically reducing the recombination loss of photogenerated electrons. This heterogeneous effect is determined by whether the particle width at half maximum (FWHM) is 500 nm. This appears to be because, in composites with a narrow particle size distribution of 500 nm or less, ceramic particles are more homogeneously dispersed on the surface of the p-type semiconductor oxide, thereby unifying the trapping and transport paths of charge carriers and effectively suppressing electron movement to defect sites that induce charge recombination.

[0055] According to a more preferred embodiment, the composite comprises the p-type semiconductor oxide and the ceramic of Formula 1 in a ratio of 0.25-0.55 mmol per 1 mol of the p-type semiconductor oxide, and the ceramic has an average particle size of 500-1,500 nm and a particle size full width at half maximum of 500 nm or less as a result of dynamic light scattering (DLS) analysis.

[0056] As described above, if the mixing molar ratio (loading amount) of the p-type semiconductor oxide and the ceramic of Formula 1 is adjusted such that the ratio of the ceramic of Formula 1 to 1 mol of the p-type semiconductor oxide is 0.25-0.55 mmol, and at the same time (ii) the ball milling conditions of the ceramic are adjusted together to have (ii-1) an average crystal size of 40-50 nm, (ii-2) an average particle size of 500-1,500 nm, and (iii-3) a particle size full width at half maximum of 500 nm or less, then, unlike cases where any of the above conditions are not satisfied, the photocathode containing such a composite shows a performance in which the photocurrent density increases significantly as a result of Linear Sweep Voltammetry (LSV) analysis, which may be more desirable.

[0057] Another aspect of the present invention relates to a photoactive material comprising a composite according to various embodiments of the present invention.

[0058] Non-limiting examples of the photoactive material according to the present invention include, but are not limited to, photoelectrodes or photocatalysts. The photoelectrode may be formed by a thin film layer comprising the composite according to the present invention formed on at least a portion of the surface of a substrate, and the photocatalyst may be formed by the composite according to the present invention being supported on a carrier.

[0059] In this regard, the present invention relates to a photocathode comprising (b) a substrate and (a) a photocathode layer formed on at least a portion of the surface of the substrate, wherein the photocathode layer may comprise a composite according to various embodiments of the present invention.

[0060] At this time, the above-mentioned material includes a conductive substrate, and the conductive substrate may be formed of a transparent conductive oxide such as fluorine-doped tin oxide (FTO) or indium tin oxide (ITO), or a conductive metal substrate.

[0061] In one preferred embodiment, the conductive substrate is an FTO-coated glass substrate to allow light transmission toward the photocathode layer. The FTO-coated glass substrate provides high transparency and excellent electrical conductivity simultaneously, making it suitable for photoelectrochemical hydrogen generation reactions. Additionally, an ITO-coated glass substrate can also provide similar characteristics and is applicable to the present invention.

[0062] In one embodiment, the thickness of the photocathode layer is 0.5 to 2.0 μm, which is preferable in that it can synergistically improve the performance of the photocathode by organically combining with the configuration according to various embodiments of the present invention. If the thickness of the photocathode layer is less than 0.5 μm, sufficient light absorption may not occur, and if it exceeds 2.0 μm, the charge transport distance increases, which may lead to greater recombination loss.

[0063] In another embodiment, the photocathode is for a hydrogen evolution reaction (HER). Since Cu2O is a p-type semiconductor and its conduction band position has a negative value compared to the hydrogen reduction potential, it is suitable for generating hydrogen gas by reducing protons at the electrode-electrolyte interface using photogenerated electrons.

[0064] Another aspect of the present invention relates to a photoelectrochemical (PEC) cell comprising (i) a working electrode, (ii) a counter electrode, and (iii) a reference electrode, wherein the working electrode is a photocathode according to various embodiments of the present invention.

[0065] In the photoelectrochemical cell according to the present invention, the counter electrode may be a platinum (Pt) electrode and the reference electrode may be a saturated Ag / AgCl electrode, but is not limited thereto.

[0066] Another aspect of the present invention relates to a water splitting device comprising a photoelectrochemical cell according to various embodiments of the present invention.

[0067] In addition, another aspect of the present invention relates to a hydrogen generation device comprising a photoelectrochemical cell according to various embodiments of the present invention. In this case, the composite according to the present invention may be applied to a working electrode and configured to generate hydrogen at the working electrode (photocathode).

[0068] In addition, another aspect of the present invention may be a multifunctional material comprising a composite according to various embodiments of the present invention. In the present invention, non-limiting examples of the multifunctional material include, but are not limited to, photoelectrodes, photocatalysts, electrochemical catalysts, sensors, supercapacitors, etc.

[0069] In addition, another aspect of the present invention relates to a device comprising a multifunctional material according to various embodiments of the present invention, which can be utilized as a gas generating device, a photoelectrochemical water splitting device, an electrochemical water electrolysis device, an electricity generating device such as a fuel cell, an energy storage device including a battery or a supercapacitor, or a communication or transportation device including one or more of these.

[0070] Another aspect of the present invention relates to a method for manufacturing a photocathode comprising the following steps.

[0071] (A) A step of forming a coating layer by coating a substrate with a mixed solution comprising (a1) a p-type semiconductor oxide precursor and (a2) a dispersion of ball-milled ceramic powder represented by the chemical formula 1;

[0072] (B) a step of heating the coating solution layer to form a coating layer; and

[0073] (C) A step of forming a photocathode layer by firing the above coating layer in an inert atmosphere.

[0074] According to one embodiment, the p-type semiconductor oxide precursor may be selected from copper(II) nitrate trihydrate (Cu(NO3)2·3H2O), copper(II) acetate (Cu(CH3COO)2), copper(II) chloride (CuCl2), and mixtures of two or more of these. Preferably, copper(II) nitrate trihydrate has excellent solubility and is cleanly converted to Cu2O upon thermal decomposition, which can improve the quality of the photocathode.

[0075] According to another embodiment, the mixed solution contains the p-type semiconductor oxide precursor and the ceramic of Formula 1 in a molar ratio of 1 mol : 0.05-3 mmol.

[0076] However, if the above mixed solution contains the above p-type semiconductor oxide precursor and the ceramic of the above chemical formula 1 in a molar ratio of 1 mol : 0.1-1 mmol, it is desirable in that the range of performance control of the photocathode is widened, allowing for the production of a photocathode suitable for various application conditions.

[0077] If the value is below the lower limit of the above range or exceeds the upper limit, the effect of improving electron mobility at the electrode-electrolyte interface and charge carrier separation efficiency of the electrode containing the composite may not be significant compared to a pure p-type semiconductor electrode, which is undesirable.

[0078] According to another embodiment, the ball-milled powder of the ceramic is obtained by performing ball milling at 400-700 rpm for 3-36 hours. Such ball milling conditions are associated with the average crystal size of the ceramic described above, and it is preferable that the ceramic have an average particle size of 500-1,500 nm and a particle width at half maximum of 1,000 nm or less as a result of dynamic light scattering (DLS) analysis. In particular, when the ball milling conditions are 400-700 rpm and 3-36 hours, the ceramic becomes uniform to have an average particle size of 500-1,500 nm and a particle width at half maximum of 1,000 nm or less, which may be advantageous for further improving photoelectrochemical performance when utilized in a photocathode.

[0079] According to a preferred embodiment, the mixed solution is a binder-free solution. Another significance of the present invention is that, according to the method of preparation of the present invention, excellent effects can be obtained without using a binder, which was essential in conventional methods. By not using a binder, insulating components within the photocathode layer are removed, making charge transport smoother and improving photoelectrochemical performance.

[0080] Non-limiting examples of methods for performing the above coating include, but are not limited to, electrostatic spray deposition (ESD), spin coating, doctor blade coating, and inkjet printing. However, according to a more preferred embodiment, it is highly desirable for the coating to be performed by an electrostatic spray deposition (ESD) method in terms of thickness uniformity, film density, and surface smoothness.

[0081] However, when the above electrostatic spray deposition is performed under the conditions of ① flow rate 20-80 μL / min, ② applied voltage 12-25 kV, ③ nozzle-substrate distance 5-25 cm, ④ deposition time 15-50 min, and ⑤ deposition temperature 80-140 ℃, it is desirable in that the thickness uniformity, film density, and surface smoothness of the thin film are optimized and the photoelectrochemical performance can be maximized.

[0082] According to another embodiment, the heating is performed at 150-500°C for 40 minutes to 5 hours, and the calcination is performed at 400-500°C for 1-3 hours under an inert atmosphere (N2).

[0083] The heating step after coating is desirable to remove residual solvent traces and increase the adhesion of the ceramic of Formula 1, and is particularly more desirable to perform at a temperature of 150-350°C for 40 minutes to 5 hours.

[0084] In addition, it is desirable to perform an additional calcination step after heating, and it is even more desirable to perform it for 1 to 3 hours at a temperature of 400-500 °C under an inert atmosphere (e.g., N2). Calcination in an inert atmosphere is important for maintaining p-type semiconductor characteristics by preventing Cu2O from being oxidized to CuO.

[0085] According to another embodiment, the mixed solution further contains one or more substances selected from ethylene glycol, propylene glycol, glycerol, and polyethylene glycol in an amount of 5-20 volume% relative to the total volume of the solution. These additives serve to improve spray stability, droplet formation, and thin film adhesion.

[0086] According to another embodiment, the concentration of the p-type semiconductor oxide precursor is 0.05-0.3 M. If the precursor concentration is less than 0.05 M, it may be difficult to form a photocathode layer of sufficient thickness, and if it exceeds 0.3 M, the viscosity of the solution increases, making it difficult to achieve a uniform coating during electrostatic spray deposition.

[0087] The present invention relates to a photoelectrochemical photocathode for hydrogen generation, and more specifically, to a p-type semiconductor / ceramic composite photocathode of Formula 1 manufactured by a scalable electrostatic spray deposition (ESD) method capable of efficiently generating hydrogen under light irradiation.

[0088] As illustrated in FIG. 1, the photocathode (100) according to the present invention comprises a conductive substrate (110), a p-type semiconductor-based photoactive layer (120) formed on the conductive substrate (110), and a ceramic-containing component (130) of Formula 1 integrated with the p-type semiconductor-based photoactive layer (120).

[0089] The photocathode (100) is composed of a flat or large-area electrode structure suitable for scale-up and mass production by electrostatic spray deposition.

[0090] The conductive substrate (110) serves as a current collector and mechanical support for the photocathode (100). The conductive substrate (110) may be formed from a transparent conductive oxide, such as fluorine-doped tin oxide (FTO) or indium tin oxide (ITO), or a conductive metal substrate. In one preferred embodiment, the conductive substrate (110) is an FTO-coated glass substrate to allow light transmission toward the photoactive layer (120).

[0091] A p-type semiconductor-based photoactive layer (120) is formed directly on a conductive substrate (110) by electrostatic spray deposition and functions as a p-type semiconductor photocathode for a hydrogen generation reaction. The p-type semiconductor-based photoactive layer (120) absorbs incident light to generate photogenerated electrons and holes, whereby the photogenerated electrons move to the surface of the photocathode to reduce protons in the electrolyte and generate hydrogen gas.

[0092] The p-type semiconductor-based photoactive layer (120) may have a porous, cylindrical, or nanostructured form formed by controlled spraying conditions, thereby increasing the effective surface area and facilitating charge transport. The thickness of the p-type semiconductor-based photoactive layer (120) can be controlled by the deposition time and spraying parameters of the electrostatic spray deposition process.

[0093] The ceramic-containing component (130) of Formula 1 is incorporated into or formed on the p-type semiconductor-based photoactive layer (120) during or after the electrostatic spray deposition process. The ceramic-containing component (130) of Formula 1 may be uniformly dispersed within the p-type semiconductor-based photoactive layer (120), partially embedded within it, or formed as a discontinuous or continuous layer on the surface of the p-type semiconductor-based photoactive layer (120).

[0094] The ceramic-containing component (130) of the above chemical formula 1 forms an interface contact region with the p-type semiconductor-based photoactive layer (120) to promote the efficient transfer of photogenerated electrons and suppress the recombination of charge carriers. Through this composite structure, the photocathode (100) exhibits improved charge separation efficiency and improved hydrogen generation activity.

[0095] Optionally, the photocathode (100) may further comprise a protective layer (140) formed on a p-type semiconductor-based photoactive layer (120) or a ceramic-containing component (130) of Formula 1. The protective layer (140) may be formed of a metal oxide or semiconductor material and is configured to improve the chemical stability of the photocathode (100) during photoelectrochemical operation while maintaining electron transport for the hydrogen generation reaction.

[0096] During operation, incident light (L) is irradiated onto the photocathode (100) through the conductive substrate (110). Photogenerated electrons generated in the p-type semiconductor-based photoactive layer (120) are transferred to the electrode-electrolyte interface through the ceramic-containing component (130) of Formula 1, where protons are reduced to produce hydrogen gas (H2). The conductive substrate (110) is electrically connected to an external circuit to enable continuous photoelectrochemical hydrogen production.

[0097] The electrostatic spray deposition method adopted in the present invention enables uniform coating over a large area, precise control of thin film thickness, and compatibility with roll-to-roll or batch processes, thereby providing excellent scalability and industrial applicability of the p-type semiconductor / ceramic photocathode structure of Formula 1.

[0098] According to one aspect of the present invention, the ceramic of Formula 1 may be used as a composite with a p-type semiconductor oxide according to various aspects and embodiments of the present invention to form a photocathode, particularly for a hydrogen evolution reaction (HER); a photoelectrochemical cell, particularly for water splitting or hydrogen evolution; and various other multifunctional materials.

[0099] If some of the components constituting the ceramic are omitted or fall outside the compositional range, it is undesirable in that the effects according to various aspects and embodiments of the present invention cannot be fully expressed.

[0100] In particular, if some of the components constituting the ceramic are omitted or fall outside the compositional range, unlike the ceramic of the composition according to the present invention, it is not effective for charge carrier separation, and thus the synergistic effect between the p-type semiconductor and the ceramic may not be observed.

[0101] It is evident that the scope of the present invention includes not only composites comprising a ceramic and a p-type semiconductor oxide in which the Cu doping amount in Formula 1 is controlled, for example, to 2.1-9.9, but also known composites comprising a ceramic and a p-type semiconductor oxide in which the Cu doping amount in Formula 1 is lower than that thereof.

[0102] However, the composite comprising the ceramic of Formula 1 and the p-type semiconductor oxide with an increased doping amount of Cu according to the present invention is more preferable because, when applied as a photoactive material for a hydrogen generation reaction, the catalytic activity is significantly increased compared to the composite comprising the ceramic of Formula 1 and the p-type semiconductor oxide prepared by the conventional method.

[0103] The ceramic-containing component (130) of the above chemical formula 1 is synthesized by an improved solid-state synthesis process to increase phase purity and electrical conductivity. Additionally, the ceramic-containing component (130) of the above chemical formula 1 may undergo mechanical processing, including ball milling, under specified conditions.

[0104] Ball milling conditions, such as milling time, rotation speed, and processing atmosphere, are controlled to adjust particle size and improve electron transport properties. Through this treatment, the ceramic-containing component (130) of Formula 1 exhibits improved electrical conductivity.

[0105] When integrated with a p-type semiconductor base layer, the ceramic-containing component (130) of Formula 1 promotes efficient charge carrier transport and inhibits the recombination of photogenerated charge carriers.

[0106] When light is irradiated onto the photocathode, the p-type semiconductor-based photoactive layer (120) absorbs photons to generate electron-hole pairs. The photogenerated electrons are transported toward the surface of the photocathode through the p-type semiconductor / ceramic composite structure of Formula 1.

[0107] The presence of the ceramic-containing component (130) of the above chemical formula 1 improves charge separation and enhances surface catalytic activity for proton reduction. Thus, the photocathode effectively catalyzes the hydrogen evolution reaction (HER) at the interface between the photocathode and the electrolyte.

[0108] Looking at the electron transfer mechanism in the Cu2O / ceramic composite of Chemical Formula 1 above, when light is irradiated, electrons are excited from the valence band (VB) of Cu2O to the conduction band (CB), and these photogenerated electrons are rapidly transferred through the ceramic of Chemical Formula 1 above to reduce protons at the electrode-electrolyte interface to generate hydrogen gas. At the same time, holes move to the counter electrode through the external circuit.

[0109] Consequently, the p-type semiconductor / ceramic composite photocathode of Formula 1 exhibits improved photoelectrochemical hydrogen generation performance compared to a photocathode containing only a p-type semiconductor. This performance enhancement is attributed to the synergistic interaction between the p-type semiconductor and the ceramic of Formula 1, which promotes efficient charge separation and transport, increases charge carrier density, suppresses interfacial recombination, and accelerates surface proton reduction kinetics.

[0110] The present invention is to be explained in more detail below through examples, etc.; however, the scope and content of the present invention shall not be interpreted as being narrowed or limited by the examples, etc. below. Furthermore, based on the disclosure of the present invention including the examples below, it is evident that a person skilled in the art can easily practice the present invention even without specific experimental results presented, and it is natural that such variations and modifications fall within the scope of the appended claims.

[0111] Furthermore, the experimental results presented below describe only the representative experimental results of the above examples and comparative examples, and the respective effects of various embodiments of the present invention not explicitly presented below will be described in detail in the relevant sections.

[0112] Examples

[0113] chemical

[0114] Copper(II) nitrate trihydrate (Cu(NO3)2·3H2O, ≥99%), absolute ethanol, ethylene glycol, and ceramic powder were used as obtained without further purification. Fluorine-doped tin oxide (FTO) coated glass substrates were used as conductive substrates. All chemicals used were AR grade and were used without further purification.

[0115] Preparation Example 1: Cu 2 Preparation of precursor solution and ceramic dispersion

[0116] (1) Preparation of Cu2O precursor solution

[0117] A 0.05-0.3 M copper precursor solution was prepared by dissolving an appropriate amount of Cu(NO3)2·3H2O in absolute ethanol while continuously stirring at room temperature. 5-20 volume% ethylene glycol was added to the solution to improve spray stability, droplet formation, and thin film adhesion. The resulting clear blue solution was stirred for 20-50 minutes prior to deposition.

[0118] (2) Ceramic manufacturing

[0119] Powders of PbO, PbSO4, Cu, and P were prepared in the molar ratio of the molecule to be synthesized and uniformly mixed. The mixture was placed in a reaction tube (quartz or copper tube), vacuum was created, and the tube was sealed. The reaction was carried out by heating at 770 °C for 12 hours in the first stage. After the reaction was completed, the granules formed in the reaction tube were powdered, and the pressure was reduced to a near-vacuum state and heated at 550 °C for 5 hours in the second stage. Through this process, solid sulfur was sublimated, and the ceramic was manufactured by removing the sublimated sulfur in the molar ratio through an evacuation process.

[0120] For example, when synthesizing a ceramic with a Cu doping amount controlled to 2 moles, the raw materials are mixed with a molar ratio of PbO : PbSO4 : Cu : P = 2 : 6 : 2 : 6, and as another example, the composition is Pb 7.38 Cu 2.62 (PO4) 5.46 (SO4) 0.54 O 0.66 S 0.84 When synthesizing the phosphorus ceramic, the raw materials were mixed with a molar ratio of PbO : PbSO₄ : Cu : P = 1.38 : 6 : 2.62 : 6.

[0121] (3) Preparation of ball-milled powder and ball-milled solution of ceramics

[0122] Manufactured Pb 7.38 Cu 2.62 (PO4) 5.46 (SO4) 0.54 O 0.66 S 0.84 A ceramic (structure confirmed via XPS and XRD, molecular weight 2,303) was ball-milled at 400-600 rpm for 3-6 hours to obtain ball-milled powder of the ceramic.

[0123] The obtained ceramic powder was dispersed in ethanol at a concentration of 1-5 mg / mL and stirred for a long time (preferably overnight) to obtain a homogeneous ceramic dispersion.

[0124] Comparative Manufacturing Example 1: Ceramic Manufacturing

[0125] Pb9Cu(PO4)6O (CAS No. 2972464-09-6) was prepared according to a known method, such as Chemistry of Materials (2024), 36(1), 275-285.

[0126] Comparative Manufacturing Example 2: Ceramic Manufacturing

[0127] Pb9Cu(PO4) according to the method described in Korean Published Patent No. 10-2023-0030188 (Patent Application No. 10-2021-0112104) 5.5 (SO4) 0.5 S 3.5 Manufactured.

[0128] Comparative Example 1: Pristine Cu 2 O Photocathode Manufacturing

[0129] The Cu2O precursor solution prepared in Preparation Example 1 was injected into a syringe and then coated onto an FTO substrate by electrostatic spray deposition (ESD) under the conditions of Table 1 below.

[0130] parameters Condition range Spray coating volume (mL) 1-5 Flow rate (μL / min) 20-80 Deposition time (min) 15-50 Distance between nozzle and substrate (cm) 5-25 Nozzle size (gauge) 21-29 Deposition temperature (°C) 80-140 Applied voltage (kV) 12-25

[0131] The FTO substrate was heated during deposition to promote solvent evaporation and precursor decomposition. To control the thin film thickness, the deposition time was between 15 and 50 minutes. After deposition, the fabricated thin film was annealed in a tubular furnace at 400-500 °C for 1-3 hours under an inert atmosphere (N2).

[0132] Example 1: Cu 2 O / Ceramic Composite Photocathode Fabrication

[0133] The ceramic dispersion prepared above was used without further purification. In addition, the Cu2O precursor solution (clear blue) prepared above was stirred for 20-50 minutes before deposition to ensure complete dissolution and homogeneity.

[0134] The mixed solution prepared by mixing the Cu2O precursor solution and the ceramic dispersion was injected into a syringe, but the mixing ratio of the Cu2O precursor solution and the ceramic dispersion was varied for each solution so that the ceramic contained 0.1-0.2 mmol, 0.3-0.4 mmol, 0.5-0.6 mmol, and 0.7-0.8 mmol, respectively, based on 1 mol of Cu2O precursor.

[0135] The mixed solution was coated onto an FTO substrate by electrostatic spray deposition (ESD), with the mixed solution supplied through a nozzle at a flow rate of 20-80 μL per minute. A high voltage in the range of 12-25 kV was applied between the nozzle and the grounded substrate, and the nozzle-substrate distance was maintained in the range of 5-25 cm.

[0136] During deposition, the FTO substrate was maintained at 70-120 °C to promote rapid evaporation of the solvent and thermal decomposition of the precursor, thereby enabling the formation of a copper oxide-based photoactive layer. Deposition was performed for 15-50 minutes to control the thickness of the deposited thin film.

[0137] After the electrostatic spray deposition was completed, the resulting thin film was subjected to a post-annealing process in a tubular furnace at a temperature of 400-500 °C for 1-3 hours under an inert atmosphere such as nitrogen (N2). Through this annealing process, the copper oxide paper in the deposited layer was converted into a p-type semiconductor-based crystalline phase suitable for use as a photocathode in photoelectrochemical applications.

[0138] Comparative Examples 2 and 3: Cu 2 O / Ceramic Composite Photocathode Fabrication

[0139] A Cu2O / ceramic composite photocathode was prepared in the same manner as in Example 1, except that the ceramic prepared in Comparative Examples 1 and 2 was used instead of the ceramic prepared in Example 1 (Comparative Examples 2 and 3, respectively).

[0140] Test Example 1: Scanning Electron Microscope (SEM) Analysis

[0141] SEM analysis was performed on the pure Cu2O prepared in Comparative Example 1 and the Cu2O / ceramic composite prepared in Example 1, and the results are presented in Figure 2.

[0142] Figures 2a and 2b are SEM images of pure Cu2O, showing a spherical shape composed of round particles of 20-40 nm in size uniformly distributed on an FTO substrate.

[0143] Additionally, Figures 2d and 2e are images of a Cu2O / ceramic composite sample, showing spherical Cu2O particles homogeneously anchored to the Cu2O surface, exhibiting an agglomerated and interconnected form. A smooth surface of the agglomerated particles was observed, and the particle size was approximately 30–50 nm.

[0144] As shown in the test examples below, it was confirmed that introducing ceramics into Cu2O particles alters the behavior of the composite in a multi-channel environment and promotes efficient charge interactions, effectively separating photogenerated carriers and consequently improving photoelectrochemical performance.

[0145] Additionally, Figures 2c and 2f are cross-sectional views of pure Cu2O and Cu2O / ceramic composite photocathodes, respectively, and Figure 2c shows that the surface of the FTO substrate is uniformly coated with a Cu2O film with a thickness of 0.6-0.7 μm. Also, Figure 2f shows a cross-sectional image of a Cu2O / ceramic composite with a thickness range of 0.7-0.8 μm, indicating that an increase in thickness occurred as a result of adding ceramic to Cu2O.

[0146] Test Example 2: X-ray Photoelectron Spectroscopy (XPS) Analysis

[0147] XPS analysis was performed on the Cu2O / ceramic composite photocathode, and the results are presented in Figure 3.

[0148] In the Cu2p spectrum of Fig. 3a, Cu2p 3 / 2 and Cu2p1 / 2 Peaks corresponding to were observed at approximately 932.5 eV and 952.3 eV, respectively, which corresponds to Cu + It indicates the oxidation state and shows the presence of the Cu2O phase. The O1s spectrum in Fig. 3b shows peaks corresponding to lattice oxygen and surface adsorbed oxygen.

[0149] Also, in the Pb4f spectrum of Fig. 3c, Pb4f 7 / 2 and Pb4f 5 / 2 Peaks corresponding to [the values] were observed at approximately 138.2 eV and 143.1 eV, respectively, indicating the presence of ceramic components. The peak observed at approximately 168 eV in the S2p spectrum of Fig. 3d indicates the presence of sulfur in the complex.

[0150] These XPS analysis results confirm that a Cu2O / ceramic composite structure was successfully formed through the uniform bonding of Cu, Pb, O, S, and P.

[0151] Test Example 3: Photoelectrochemical measurement

[0152] The photoelectrochemical (PEC) hydrogen evolution reaction (HER) performance of the photocathode was evaluated using a standard three-electrode configuration in an optical electrolytic cell connected to a multichannel potentiostat.

[0153] In this configuration, the prepared photocathode was used as the working electrode, a platinum foil as the counter electrode, and a saturated Ag / AgCl electrode as the reference electrode. For all measurements, 0.5 M Na2SO4, an aqueous electrolyte suitable for hydrogen generation, was used.

[0154] PEC measurements were performed in a high-purity quartz cell to ensure uniform light transmission to the electrode surface. A 300 W xenon (Xe) lamp was used as a simulated sunlight source, and a standard silicon reference cell was used to calibrate to 1 sun (100 mW / cm²).

[0155] Linear scanning potential (LSV) was performed under chopped light illumination to evaluate the photocurrent response and HER activity of the photocathode.

[0156] Test Example 4: Linear Scanning Potential (LSV) Analysis

[0157] The photoelectrochemical (PEC) performance of the pure Cu2O photocathode prepared in Comparative Example 1 and the Cu2O / ceramic composite photocathode prepared in Example 1 was evaluated using Linear Sweep Voltammetry (LSV).

[0158] As illustrated in Figures 4a and 4b, the Cu2O / ceramic composite photocathode exhibits a substantially increased photocurrent density under light irradiation during the hydrogen evolution reaction. Under the same measurement conditions, the photocurrent density of the Cu2O / ceramic photocathode was observed to be about twice that of the pure Cu2O photocathode.

[0159] These improvements are attributed to the presence of a ceramic-containing component (130) that improves charge separation efficiency, facilitates electron transport from the p-type semiconductor-based photoactive layer (120) to the electrode-electrolyte interface, and reduces recombination losses.

[0160] On the other hand, the introduction of ceramics significantly reduced charge transfer resistance compared to pure Cu2O, implying that the introduction of ceramics reduced resistance by increasing charge carrier density and electrical conductivity.

[0161] Finally, it was confirmed that the synergistic effect of Cu2O and ceramics is highly effective for excellent charge carrier separation and can ultimately improve overall hydrogen generation performance.

[0162] As a result of comparative experiments between the Cu2O / ceramic composite photocathodes prepared in Comparative Examples 2 and 3, respectively, and the composite photocathode prepared in Example 1, the Cu2O / ceramic composite photocathode of Example 1 showed approximately -0.07 mA / cm² at -0.3 V vs Ag / AgCl. 2The above photocurrent density was observed, showing a photocurrent density approximately twice as high as that of pure Cu2O, and not only did it exhibit a fast and stable photocurrent response in the photo-on-off cutting response, but a synergistic effect was also observed in which effective transfer of photogenerated electrons and suppression of charge recombination occurred at the interface between Cu2O and ceramic.

[0163] In contrast, for the composite photocathode of Comparative Example 2 and the composite photocathode of Comparative Example 3, the photocurrent density at -0.3 V vs Ag / AgCl was approximately -0.04 mA / cm², respectively. 2 and about -0.045 mA / cm 2 As such, it is preferable to use composites of various embodiments of the present invention including the composite of Example 1, as the photoelectrochemical performance enhancement effect remains at a level similar to pure Cu2O and is not effective in separating charge carriers, so no synergistic effect between Cu2O and ceramic is observed. Explanation of the symbols

[0164] 100: Photocathode 110: Conductive substrate 120: p-type semiconductor-based photoactive layer 130: Ceramic-containing components 140: Protective layer (optional) L: Incident light H2: Hydrogen gas

Claims

Claim 1 Composite for a photocathode for a hydrogen evolution reaction via photoelectrochemical water splitting, comprising a p-type semiconductor oxide and a ceramic of the following Formula 1: [Formula 1]Pb 10-x Cu x [(PO4) 6-y (SO4) y ]O z S z' x is a real number between 0.9 and 9.9, and y is 10 -10 It is a real number from 5.9 to 10, where z and z' are each 10 -10 It is a real number between 4 and 10, and z+z' is 10 -10 It is a mistake of up to 4. Claim 2 In claim 1, the p-type semiconductor oxide is a composite selected from Cu2O, CuO, Cu2O / CuO composite, NiO, Co3O4, and combinations of two or more of these. Claim 3 In claim 1, the above x is a complex of 2.1-9.

9. Claim 4 In claim 1, the complex comprises the p-type semiconductor oxide and the ceramic of Formula 1 in a ratio of 0.04 to 400 mmol based on 1 mol of the p-type semiconductor oxide. Claim 5 In claim 1, as a result of X-ray photoelectron spectroscopy (XPS) analysis, the composite is Cu(2p 3 / 2 A complex in which peaks of ), Pb(4f), S(2p), and P(2p) are detected. Claim 6 In claim 1, based on dynamic light scattering (DLS) analysis results, the ceramic is a composite having an average particle size of 500-1,500 nm and a particle size full width at half maximum of 1,000 nm or less. Claim 7 A photoactive material for a hydrogen generation reaction photocathode through photoelectrochemical water splitting, comprising a composite according to any one of claims 1 to 6. Claim 8 (a) a substrate, and (b) a photocathode formed on at least a portion of the surface of the substrate, a photocathode for a hydrogen generation reaction through photoelectrochemical water splitting, wherein the photocathode comprises a composite according to any one of claims 1 to 6. Claim 9 In claim 8, the above description is a photocathode selected from a fluorine-doped tin oxide (FTO) coated glass substrate or an indium tin oxide (ITO) coated glass substrate. Claim 10 In claim 8, the photocathode has a photocathode layer thickness of 0.5-2.0 μm. Claim 11 delete Claim 12 A photoelectrochemical (PEC) water splitting cell comprising (i) a working electrode, (ii) a counter electrode, and (iii) a reference electrode, wherein the working electrode is a photocathode for a hydrogen generation reaction through photoelectrochemical water splitting according to claim 8. Claim 13 A water splitting device comprising a photoelectrochemical water splitting cell according to paragraph 12. Claim 14 A method for manufacturing a photocathode for a hydrogen generation reaction photocathode via photoelectrochemical water splitting, comprising the following steps: (A) forming a coating layer by coating a substrate with a mixed solution comprising (a1) a p-type semiconductor oxide precursor and (a2) a dispersion of ball-milled ceramic powder represented by the following Chemical Formula 1; (B) forming a coating layer by heating the coating layer; and (C) forming a photocathode layer by firing the coating layer in an inert atmosphere: [Chemical Formula 1]Pb 10-x Cu x [(PO4) 6-y (SO4) y ]O z S z' x is a real number between 0.9 and 9.9, and y is 10 -10 It is a real number from 5.9 to 10, where z and z' are each 10 -10 It is a real number between 4 and 10, and z+z' is 10 -10 It is a mistake of up to 4. Claim 15 A method for manufacturing a photocathode in claim 14, wherein the p-type semiconductor oxide precursor is selected from copper(II) nitrate trihydrate (Cu(NO3)2·3H2O), copper(II) chloride (CuCl2), copper(II) acetate (Cu(CH3COO)2), and a mixture of two or more of these. Claim 16 A method for manufacturing a photocathode according to claim 14, wherein the mixed solution comprises the p-type semiconductor oxide precursor and the ceramic of Formula 1 in a molar ratio of 1 mol : 0.05-3 mmol. Claim 17 A method for manufacturing a photocathode according to claim 14, wherein the ball-milled powder of the ceramic is obtained by performing ball milling at 400-700 rpm for 3-36 hours. Claim 18 A method for manufacturing a photocathode in which the above-mentioned mixed solution is a binder-free solution, wherein in claim 14. Claim 19 In claim 14, the above coating is a method for manufacturing a photocathode performed by an electrostatic spray deposition (ESD) method. Claim 20 A method for manufacturing a photocathode according to claim 14, wherein the heating is performed at 150-500 ℃ for 40 minutes to 5 hours, and the calcination is performed at 400-500 ℃ for 1-3 hours under an inert atmosphere. Claim 21 A method for manufacturing a photocathode according to claim 14, wherein the mixed solution further comprises one or more substances selected from ethylene glycol, propylene glycol, glycerol, and polyethylene glycol in an amount of 5-20 volume% relative to the total volume of the solution. Claim 22 A method for manufacturing a photocathode according to claim 14, wherein the concentration of the p-type semiconductor oxide precursor is 0.05-0.3 M.

Citation Information

Patent Citations

  • Semiconductor electrode and photoelectric conversion element

    JP2001076778A

  • Dye-sensitized solar cell

    JP2007265634A

  • Photo-electrode of dye-sensitized solar cell And Method for producing of the photo-electrode of dye-sensitized solar cell

    KR1020120012202A

  • Ceramic composite with superconductivities over room temperature at atmospheric condition and mehtod of manufacturing the ceramic composite

    KR1020230030188A